(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective To establish the association of the SEPP1 gene’s (rs7579) polymorphism with enzymatic, metabolic and hormonal activity in patients with chronic pancreatitis (CP) and primary hypothyroidism. Materials and methods Eighty CP patients (40 with comorbid hypothyroidism) and 30 healthy controls participated in the case-control study. Pancreatic enzymes, Selenoprotein P, NO metabolites (NO2 -+NO3 -), glucose, total cholesterol (TC), triglycerides (TG) and low/high density lipoprotein cholesterol (LDL-, HDL-C), Atherogenicity Index (AI), thyroid-stimulating hormone (TSH), Thyroxine (T4), glomerular filtration rate (GFR) were studied. SEPP1 (rs7579) genotyping performed by PCR (FlexCycler BU). Results and discussion SEPP1 (rs7579) gene’s A-allele increases the risk of hypothyroidism twice in CP [OR=2.0; OR 95%CI:1.09-3.66; р=0.023]. Pancreatic patients with hypothyroidism and SEPP1 gene’s (rs7579) AA-genotype had 60.0% (рАА=0.013) lower elastase and 13.78% (р=0.003) higher α-amylase as well as TSH by 10.81% (рАА=0.009) and 15.64% (рАА=0.009), especially in women 14.55-45.18% (р<0.001) at a lower value of Selenoprotein P – by 28.65-48.08% (р≤0.048) regardless of the SEPP1 gene (rs7579) variants. Women have 17.43-18.14% (pW≤0.032) higher NO metabolites than men; A-allele women have free T4 value 2.62 times lower (рGG=0.01) than GGwomen and 2.97 times lower (рW=0.011) than men. Comorbid patients with A-allele had elevated TC and LDL-C, by 11.77-26.45% (рАА≤0.01) and 18.06-26.21% (рАА≤0.019), respectively. Women have 54.50% (pW=0.002) higher AI with 39.30% lower (pW=0.034) Selenoprotein P and 21.96-24.56% (pW≤0.033) GFR than men. Conclusion SEPP1 (rs7579) gene polymorphism influences the risk of hypothyroidism in CP patients, changes of pancreatic enzymes, dyslipidaemia particular in AA-genotype carriers, mainly women. There was no dependence of SEPP1 and total NO metabolites values on the SEPP1 gene (rs7579) polymorphism. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1038-1047